Nationalism and imperialism in South and Southeast Asia essays presented to Damodar R. SarDesai - Kaminsky, Arnold P.; Long, Roger D. (Routledge, Taylor & Francis Group, 2017)
This volume is a festschrift for Damodar Ramaji SarDesai (b. 1931). The volume includes a biographical introduction and a bibliographic essay on SarDesai's major writings and contains new and cutting-edge essays on the design of imperial Vijayanagara; famine policy in colonial India and how European imperialist policies created, or exacerbated the impact of, famines.